Management of take-all disease caused by Gaeumannomyces graminis var. tritici in wheat through Bacillus subtilis strains - Zhao, Gangyi; Sun, Tianjie; Zhang, Zina; Zhang, Jingjing; Bian, Yinbo; Hou, Chunyan; Zhang, Dongdong; Han, Shengfang; Wang, Dongmei (Frontiers in Microbiology, 2023)
Wheat (Triticum aestivum) is the second largest grain crop worldwide, and one of the three major grain crops produced in China. Take-all disease, caused by Gaeumannomyces graminis var. tritici (Ggt) infection, is a widespread and devastating soil-borne disease that harms wheat production. At present, the prevention and control of wheat take-all depend largely on the application of chemical pesticides. Chemical pesticides, however, not only lead to increased drug resistance of pathogens but also leave significant residues in the soil, causing serious environmental pollution. In this study, we investigated the application of Bacillus subtilis to achieve take-all disease control in wheat while reducing pesticide application. Antagonistic bacteria were screened by plate test, species identification of strains was performed by Gram staining and sequencing of 16s rDNA, secondary metabolite activity of strains was detected by clear circle method, strain compatibility and effect of compounding on Ggt were detected by plate, and the application prospects of specific strains were analyzed by greenhouse and field experiments. We found that five Bacillus subtilis strains, JY122, JY214, ZY133, NW03, Z-14, had significant antagonistic effects against Ggt, and could secrete antimicrobial proteins including amylase, protease, and cellulase. Furthermore, Z-14 and JY214 cultures have also been shown to change the morphology of Ggt mycelium. These results also showed that Z-14, JY214, and their combination can control take-all disease in wheat at a reduced level of pesticide use. In summary, we screened two Bacillus spp. strains, Z-14 and JY214, that could act as antagonists that contribute to the biological control of wheat take-all disease.